Genetics of flower development in Ranunculales – a new, basal eudicot model order for studying flower evolution. Issue 2 (4th January 2017) - Damerval, Catherine; Becker, Annette
Summary: Ranunculales, the sister group to all other eudicots, encompasses species with a remarkable floral diversity, which are currently emerging as new model organisms to address questions relating to the genetic architecture of flower morphology and its evolution. These questions concern either traits only found in members of the Ranunculales or traits that have convergently evolved in other large clades of flowering plants. We present recent results obtained on floral organ identity and number, symmetry evolution and spur formation in Ranunculales species. We discuss benefits and future prospects of evo‐devo studies in Ranunculales, which can provide the opportunity to decipher the genetic architecture of novel floral traits and also to appraise the degree of conservation of genetic mechanisms involved in homoplasious traits.   Contents     Summary 361 I. Introduction 361 II. The major regulators of floral organ identity in Ranunculales 362 III. Floral diversity in Ranunculales 363 IV. Pollination modes, reproduction systems and species diversification 364 V. Conclusion: from model organisms to model orders? 364   Acknowledgements 365   References 365